The Spot Roller Rink - Moffit, Timothy E. (Senate Hall, 2007)
The Spot Roller Rink is a neglected recreational business that operates in a mature industry with seemingly little upside potential. The principle challenge is for students to serve as a business consultant to a small business entrepreneur in developing a business model that can revitalize this tired business. Students greatly enjoy working this case, since it gives them the opportunity to problem solve creatively through all facets of a small business. This case is particularly effective when assigned at the beginning of a small business management or entrepreneurship course. The case works well in developing student awareness regarding the scope of decisions that an entrepreneur must make. The focus of the case is business model development with specific idea generation and commensurate pro forma financial statement preparation. Putting numbers to ideas is a critical early step in the entrepreneurial process. This case presents students with this opportunity in a very manageable way. Not all entrepreneurial opportunities are wrapped in cutting edge technologies and revolutionary product development. A coffee shop became Starbucks, and a hamburger stand became McDonalds. Can a roller skating rink be revitalized by a young entrepreneur?
Keywords: entrepreneurship|micro enterprise|idea generation|pro forma development|revitalization